2004
DOI: 10.1515/bc.2004.122
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure of fumarylacetoacetate hydrolase family member Homo sapiens FLJ36880

Abstract: The human protein FLJ36880 belongs to the fumarylacetoacetate hydrolase family. The X-ray structure of FLJ36880 has been determined to 2.2 A resolution employing the semi-automated high-throughput structural genomics approach of the Protein Structure Factory. FLJ36880 adopts a mixed beta-sandwich roll fold and forms homodimers in crystals as well as in solution. One Mg2+ ion is bound to each subunit of the dimeric protein by coordination to three carboxylate oxygens and three water molecules. These metal bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…These structures include two putative enzymes from Thermus thermophilus HB8 (1WZO and 2DFU) ‡, 16,17 the protein YcgM (1NR9) from E. coli ‡, 18 and both the human protein FLJ36880 (1SAW) 19 and the yeast protein YNQ8_YEAST (1NKQ) ‡. 20 One biochemically characterized member is the bifunctional decarboxylase/isomerase HpcE (1I7O, 1GTT, EC 4.1.1.68/5.3.3.10) from E. coli C, which is involved in two consecutive steps of the homoprotocatechuate meta-fission pathway of aromatic compounds such as 3-and 4-hydroxyphenylacetate that ultimately leads to pyruvate and succinate.…”
Section: Fah Superfamilymentioning
confidence: 99%
“…These structures include two putative enzymes from Thermus thermophilus HB8 (1WZO and 2DFU) ‡, 16,17 the protein YcgM (1NR9) from E. coli ‡, 18 and both the human protein FLJ36880 (1SAW) 19 and the yeast protein YNQ8_YEAST (1NKQ) ‡. 20 One biochemically characterized member is the bifunctional decarboxylase/isomerase HpcE (1I7O, 1GTT, EC 4.1.1.68/5.3.3.10) from E. coli C, which is involved in two consecutive steps of the homoprotocatechuate meta-fission pathway of aromatic compounds such as 3-and 4-hydroxyphenylacetate that ultimately leads to pyruvate and succinate.…”
Section: Fah Superfamilymentioning
confidence: 99%
“…Apart from these really putative proteins, we also detected more interesting changes. Among them, a rather poorly characterized protein, homolog even at the 3-D structure level to a bacterial protein involved in the late steps of tyrosine degradation [33], and with a strong probability of mitochondrial localization.…”
Section: Other Proteinsmentioning
confidence: 99%
“…Oxaloacetate decarboxylases from prokaryotic organisms are well studied and are either soluble and divalent cation-dependent (like Cg1458) or membrane-bound and dependent on sodium and biotin (20). Molecular modeling based on the established x-ray structure of FAHD1 (9) revealed that indeed the catalytic centers of FAHD1 and Cg1458 are very similar and support a common catalytic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the structure of the active site, a hydroxylase or decarboxylase function was proposed. Also, a common function shared with other so far uncharacterized FAH proteins, E. coli YcgM and Thermus thermophilus TTHA0809, was suggested due to structural similarities (9). FAHD2 shows moderate sequence homology with FAHD1, but no further data are available for this enzyme at the moment.…”
mentioning
confidence: 98%
See 1 more Smart Citation